PENGARUH INOKULASI CAMPURAN ISOLAT BAKTERI PELARUT FOSFAT INDIGENUS RIAU TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine max L. Merr) - LUFITA NUR ALFIAH; DELITA ZUL; NELVIA NELVIA (Jurnal Agroteknologi, 2016)
At this time the oportunity increasing soybean production still open through optimize the fulfill of the nutrient of plants. Phosphorus is one of element nutrient essentiality macro those as very important to growth and development of plants. The existence it in land abundance, but the concentration P who are get reserve by plant is very low. At acid land P bunching aluminum (AI) and iron (Fe) meanwhile in land Alkhalin P bounded calsium (Ca). The increasing efesiency of supply fosfat at plant can effort with exploit microorganism soluble phosphate group. Test potential solubility P by BPF isolated from peat soil Biosphere Reserve Giam Siak Kecil Bukit Batu, Riau. Test was conducted and taken in semi-quantitative which able to dissolve Ca3 (PO4) 2, FePo4 and phosphate rock. However adaptability and potential dilution BPF origin peat soils of Riau indigenus inoculated soybean in mineral soil until now unknown. This research was conducted in order to determine the effect of inoculation BPF indigenus Riau toward growth and yield of soybean. The study was conducted in factorial experiment using completely randomized design (RAL Factorial), as the first factor is soil treatment consisting of two levels ie: T0: soil without sterilization, T1: sterilized soil. The second factor is the provision isolates BPF which consists of 4 levels, namely: B0: without inoculation, B1: 2 isolates BPF (BB_UB6 and BB_K9), B2: 3 isolates BPF (BB_UB6, BB_K9 and BB_K2), B3: 4 isolates BPF (BB_UB6, BB_K9, BB_K2, and BB_HS13). The results showed soil sterilization decrease the number of primary branch becomes 5.67 and 1.49 g dry weight of the plant. The fastest time of harvest occurs in plants without inoculation of sterile soil that is 78.78. The highest weight of 100 seeds produced by the plant without inoculation of sterile soil that is 13.17 g.